Handbook of leaving religion - Enstedt, Daniel (Brill handbooks on contemporary religion, 2020)
"The Handbook of Leaving Religion introduces a neglected field of research with the aim to outline previous and contemporary research, and suggest how the topic of leaving religion should be studied in the future. The handbook consists of three sections: 1) Major debates about leaving religion; 2) Case studies and empirical insights; and 3) Theoretical and methodological approaches. Section one provides the reader with an introduction to key terms, historical developments, major controversies and significant cases. Section two includes case studies that illustrate various processes of leaving religion from different perspectives, and each chapter provides new empirical insights. Section three discusses, presents and encourages new approaches to the study of leaving religion. Contributors are: David Belfon, Clemens Cavallin, David McConnell, Ryan T. Cragun, Carole Cusack, Daniel Enstedt, Monica Lindberg Falk, Miguel Farias, Niklas Foxeus, Philip Francis, Amorette Hinderaker, Isabella Kasselstrand, Lily Kong, Göran Larsson, Erica Li Lundqvist, Jörgen Magnusson, Teemu T. Mantsinen, Kyle Messick, Masoumeh Rahmani, Lena Roos, Caleb Schaffner, Christine Schirrmacher, Michael Stausberg, Nora Stene, Peter G. Stromberg, Ryan Szpiech, Teemu Taira, Kati Tervo-Niemelä, Hugh Turpin, Orlando Woods"--